Live cell imaging of cytoplasmic and nuclear Ca2+ dynamics in Arabidopsis roots - Krebs, Melanie; Schumacher, Karin (Cold Spring Harbor protocols, 2013)
Approaches for Ca(2+) measurement require data recording with high spatiotemporal resolution. This is achieved by combined usage of locally targeted genetically encoded calcium indicators (GECIs) and confocal laser scanning microscopy (CLSM). This protocol provides instructions for setting up a CLSM-based experiment to measure cytosolic and nuclear Ca(2+) dynamics in Arabidopsis lines expressing Yellow Cameleon Ca(2+) indicators.
Im Titel ist „2+“ hochgestellt
Gesehen am 14.08.2019